Juventude, família, temporalidade e projeto de vida : contribuições do modelo bioecológico - Valentini, Natália Abido (2020)
The present study aimed to understand how six young university students evaluate and perceive themselves in their processes of adulthood development and in the construction of their life projects, and how they locate their families in these dimensions. The design used was descriptive-exploratory, in order to enable the description of the phenomenon and its exploration from the perspective of the Bioecological Model of Human Development (MBDH). This model presents the dimensions of Process, Person, Context and Time (PPCT), providing an integral view of human development, necessary for the discussion of protective and vulnerable aspects, both individual and socio-environmental. For the research, four instruments were created and used: 1) semi-structured interview; 2) declarative game; 3) incomplete sentences game and 4) timeline. The participants were three women and three men aged between 18 and 25 years, attending undergraduate courses. From the application of the instruments and a qualitative-descriptive analysis of the information obtained, it was possible to identify elements indicated as promoters of healthy development and enabling safety and autonomy in the construction of life projects. The positive roles linked to the family are related to socio-affective support, mutual help between members and the transmission of beliefs and values. The healthy interpretation of the family function relates to the proximity of the members and the perception of care, support and welcome, favoring the development of autonomy. On the other hand, family experiences disadvantage this process when they do not encourage individual choices or when they are conflicting. In addition to the family, the information made it possible to discuss the functions of friendships and how the participants engage in activities that, in their quality, allow reflections and disalienating processes about themselves and the reality they live in. Based on theoretical references on youth, emerging adulthood, temporality, family and MBDH, it is possible to point out an oscillation between aspects that are macrosystemic and idealized and aspects identified as microsystemic and subjectivated in the life projects explained by the participants. It is perceived how access to healthy bonds, as well as to resources present in the social, historical, economic and political reality, located in the construction of the human development trajectory, is necessary so that there is, specifically for the young and emerging adult population, the strengthening of life projects and the condition of experiencing unstable modes of temporalization as experienced in contemporary times.